Insulin-Like Growth Factor (IGF)-I and Insulin in Normal and Growth-Restricted Mother/Infant Pairs - Ariadne Malamitsi-Puchner; Despina D. Briana; Dimitrios Gourgiotis; Maria Boutsikou; Karl-Philipp Puchner; Stavroula Baka; Antonios Marmarinos; Dimitrios Hassiakos (Mediators of Inflammation)
Insulin-like growth factor (IGF)-I and insulin are essential for fetal growth. We investigated perinatal changes of both factors in 40 mothers and their 20 appropriate-for-gestational-age (AGA) and 20 intrauterine-growth-restricted (IUGR) fetuses and neonates on day 1 (N1) and day 4 (N4) postpartum. Fetal and N1, but not N4, IGF-I levels were increased in AGA (P<.001 and P=.037, resp.). N1 insulin levels were lower in IUGR (P=.048). Maternal, fetal, and N1 IGF-I, and fetal insulin levels positively correlated with customized centiles (r=.374, P=.035, r=.608, P<.001, r=.485, P=.006, and r=.654, P=.021, resp.). Female infants presented elevated fetal and N4 IGF-I levels (P=.023 and P=.016, resp.). Positive correlations of maternal, fetal, and neonatal IGF-I levels, and fetal insulin levels with customized centiles underline implication of both hormones in fetal growth. IUGR infants present gradually increasing IGF-I levels. Higher IGF-I levels are documented in females.